2014
DOI: 10.5539/jas.v6n12p202
|View full text |Cite
|
Sign up to set email alerts
|

Climate Change Perception and Farmers’ Adoption of Sustainable Land Management for Robust Adaptation in Cameroon

Abstract: The certainty of a changing climate is asserted in the perception of observable changes in rainfall and temperature reported by more than 52% of farm managers in Cameroon's dry North region and almost 70% in the humid West region. Responding to these observable changes, soil and crop management techniques are adopted to ease climatic stress and insure farms from income shocks and associated vulnerabilities. Farmers were surveyed on their participation in sustainable land management (SLM) programs, and a probit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
2
2
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 39 publications
1
5
0
Order By: Relevance
“…Access to a local NGO increased the log count of the number of SLM technologies adopted by 33.2 % ceteris paribus. This corroborates earlier studies on the important role played by the NGOs in disseminating agricultural information in rural agricultural communities (Amr and Richiedei 2000;Wattenbach et al 2005;Molua 2014;Schipper et al 2014).…”
Section: Drivers Of Sustainable Land Management: Adoption Of Improvedsupporting
confidence: 80%
“…Access to a local NGO increased the log count of the number of SLM technologies adopted by 33.2 % ceteris paribus. This corroborates earlier studies on the important role played by the NGOs in disseminating agricultural information in rural agricultural communities (Amr and Richiedei 2000;Wattenbach et al 2005;Molua 2014;Schipper et al 2014).…”
Section: Drivers Of Sustainable Land Management: Adoption Of Improvedsupporting
confidence: 80%
“…This requires greater investments in climate smart practices, such as drought and heat tolerant varieties, supplemental irrigation, and integrated strategies to reduce livelihood risks (Molua, 2014;Arslan et al, 2015;Bryan et al, 2013;Howden et al, 2007). These strategies can notably reduce climate change vulnerability by making farm households better able to adjust to the changing climate, and these help to avoid or reduce potential damages (IPCC, 2014).…”
Section: The Need For Adaptation and Mitigationmentioning
confidence: 99%
“…The micro farm level adaptation are the farmers' investment in climate smart practice, focuses on farm tactical decisions in response to seasonal variations in climatic and other factors (Comoé et al 2014;Molua, 2014;Ollat & Touzard, 2014;Ollat & Touzard, 2005). This requires greater investments in climate smart practices, such as drought and heat tolerant varieties, supplemental irrigation, and integrated strategies to reduce livelihood risks (Molua, 2014;Arslan et al, 2015;Bryan et al, 2013;Howden et al, 2007).…”
Section: The Need For Adaptation and Mitigationmentioning
confidence: 99%
See 1 more Smart Citation
“…(Kihiu, 2016) estimated that in Kenya, the adoption rates of sustainable land management (SLM) practices in areas where SLM practices are highly needed (dry lands) due to unfavourable conditions are alarmingly low estimated at 14.2%, despite the declining productivity of these ecosystems. Even 20 though there is insufficient research done on adoption rates in all agro-climatic zones of Kenya, this value could be lower in semi-humid to humid zones as studies have reported that where lands are relatively productive, there is widespread apathy among small scale farmers to invest in SLM technologies as the perceived net gain is minimal (Sterve, 2010;Kirui, 2016;Molua, 2014).…”
Section: Introductionmentioning
confidence: 99%